An Evaluation of DevOps Practices to Prevent Fraud: A Case Study of PT XYZ - Adi Hartanto; Rizal Fathoni Aji (AI Society & STMIK Indonesia, 2023)
Fraudulent transactions caused mainly by high level bugs in PT XYZ’s production environment have caused significant financial losses for the company. Such issues were attributed to subpar DevOps practices in PT XYZ. Based on the given problem, this research evaluates DevOps practices in PT XYZ based on Bucena’s maturity model and proposes recommendations for improvement. This study collects data using interviews with four key figures in PT XYZ’s software development team and processed using the thematic analysis method in conjunction with magnitude coding. The results showed that PT XYZ’s primary weaknesses in implementing DevOps practices fall mostly within Technology and Process domains. From these findings, a roadmap is designed for a timeframe of 12 months, which consists of 9 primary objectives to fulfill to increase overall DevOps maturity level at PT XYZ up to the Defined level.